Cutaneous Adverse Effects Associated With the Tyrosine-Kinase Inhibitor Cabozantinib - Zuo, Rena C. (JAMA Dermatol, 2015)
IMPORTANCE: Cabozantinib S-malate is a vascular endothelial growth factor receptor 2, c-MET, and RET multitargeted tyrosine kinase inhibitor that has antiangiogenic and antitumorigenic properties with potential efficacy for the treatment of several cancers. Cutaneous reactions, one of the most frequently observed adverse effects associated with tyrosine kinase inhibitors, can significantly affect patients’ quality of life and drug adherence and represent a major therapeutic challenge to maximizing the efficacy of targeted cancer therapy. OBJECTIVE: To describe the frequency and spectrum of skin reactions in patients with urothelial carcinoma receiving cabozantinib as monotherapy. DESIGN, SETTING, AND PARTICIPANTS: A single-institution study at the Clinical Research Center at the National Institutes of Health included 41 consecutive adults with metastatic, progressive urothelial carcinoma enrolled in a National Cancer Institute open-label, nonrandomized, phase 2 clinical trial. Patients receiving cabozantinib were evaluated for the development of skin reactions at each treatment visit from October 2012 to June 2014 by the primary oncology team and referred for dermatologic evaluation as appropriate. MAIN OUTCOMES AND MEASURES: A detailed history, full-body physical examination, and clinical photographs of cutaneous lesions were obtained. RESULTS: Of 41 consecutive patients who received cabozantinib, 30 (73%) developed 1 or more cutaneous toxic effects. Adverse events included hand-foot skin reaction (22 [54%]), generalized pigment dilution and/or hair depigmentation (18 [44%]), xerosis (8 [20%]), scrotal erythema/ulceration (6 [15%]), and nail splinter hemorrhages (5 [12%]). Eighteen patients (44%) had 2 or more cutaneous adverse events. Reactions developed in 17 of 30 patients (57%) during the first month of cabozantinib treatment and in 24 of 30 (80%) by the second month. Of patients with skin toxic effects, dose reduction was required for symptom management in 9 of 30 patients (30%), and treatment discontinuation was required in 4 of 30 (13%). CONCLUSIONS AND RELEVANCE: Cabozantinib monotherapy is associated with 1 or more cutaneous adverse events in most patients. Early detection and prompt treatment may increase patients’ adherence to tyrosine kinase inhibitor therapy. TRIAL REGISTRATION: clinicaltrials.gov Identifier: